2006
DOI: 10.25249/0375-7536.200636s15158
|View full text |Cite
|
Sign up to set email alerts
|

Estudo De Inclusões Fluidas Em Mineralização Sulfetada Vulcanogênica Hidrotermal E De Ouro Orogênico Na Serra Do Ipitinga, Amazônia, Brasil

Abstract: Resumo ESTUDO DE INCLUSÕES FLUIDAS EM MINERALIZAÇÃO SULFETADA VULGANOGÊNICA HIDROTERMAL E DE OURO OROGÊNICO NA SERRA DO IPJTJNGA, AMAZÔNIA, BRASIL aGrupo Ipitinga (2,27 Ga), na serra homôni-ma, consiste em uma unidade metavulcanossedimentar, constituída por metavu1cânicas máficas e ultramáficas, rochas a cordierita-antofilita e a quartzo-clorita, às quais estão sobrepostos metassedimentos químicos (BIFs tipos óxido e silicato) e elásticos, Parte das lavas básicas foi hidrotennalmente alterada em condições simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…Klein et al (in press) reported temperatures of 475 and 447 °C for Carará and the nearby (and geologically similar) Catarino showing, respectively, based on oxygen isotope fractionation between hydrothermal quartz and muscovite. These temperatures lie close to the upper limit of the retrogressive, greenschist facies metamorphic event established by Faraco et al (2006) and likely represent the conditions of the hydrous alteration.…”
Section: Trapping Conditionssupporting
confidence: 65%
See 2 more Smart Citations
“…Klein et al (in press) reported temperatures of 475 and 447 °C for Carará and the nearby (and geologically similar) Catarino showing, respectively, based on oxygen isotope fractionation between hydrothermal quartz and muscovite. These temperatures lie close to the upper limit of the retrogressive, greenschist facies metamorphic event established by Faraco et al (2006) and likely represent the conditions of the hydrous alteration.…”
Section: Trapping Conditionssupporting
confidence: 65%
“…The dotted line represents the geothermal gradient assuming lithostatic overburden. The dark and light grey shaded areas represent the peak and retrogressive metamorphic conditions, respectively, for the hosting sequence, as determined by Faraco et al (2006). The stippled area defines the estimated predominant P-T conditions for the entrapment of the CO 2 -rich fluid and the arrowed line represents the possible P-T path followed by the CO 2 fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation